How Does Language and Culture Form One Unique National Identity? A Case Study of Renaming the South China Sea to North Natuna Sea in Indonesia’s Foreign Policy Since 2016 - Rhevy Adriade Putra (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
This article discusses the use of language and historical legacy in forming one national identity, which is thus used as a political stand of foreign policy. The primary analysis of this article uses the concept of “imagined communities,” which distinguishes one’s perception of themselves toward others. The methodology of “nationalizing the past” was adopted to amplify a more substantial justification toward what has been believed to be one’s belonging. The shift in Indonesia’s foreign policy toward the South China Sea disputes, reflected in renaming the northern side of Indonesia’s Natuna Islands as the North Natuna Sea, was selected as a case study. This article argues that language serves not only as a means to define national identity but also as a vital tool in safeguarding the national assets inherited across generations that are an integral part of their identity. Keywords: language, imagined communities, South China Sea, territorial conflict, Indonesia, foreign policy, North Natuna Sea Artikel ini membahas penggunaan bahasa dan warisan sejarah dalam membentuk sebuah identitas nasional yang kemudian digunakan sebagai sikap politik terhadap kebijakan luar negeri. Analisis utama artikel ini ini dilakukan dengan menggunakan konsep 'komunitas yang dibayangkan’ (imagined communities), yang membedakan persepsi sebuah kelompok atas dirinya terhadap yang lain. Metodologi 'menasionalisasi masa lalu’ (nationalising the past) lantas digunakan untuk memperkuat pembenaran terhadap apa yang diyakini sebagai milik sebuah negara. Pergeseran kebijakan luar negeri Indonesia terhadap sengketa Laut Tiongkok Selatan dengan menamai sisi utara Kepulauan Natuna sebagai Laut Natuna Utara diambil sebagai studi kasus. Artikel ini berargumen bahwa bahasa tidak hanya berfungsi sebagai cara untuk mendefinisikan identitas nasional, tetapi juga sebagai alat penting untuk mempertahankan aset-aset nasional yang diturunkan dari generasi ke generasi sebagai bagian penting dari identitas. Kata-kata kunci: bahasa, imagined communities, Laut Tiongkok Selatan, konflik teritorial, Indonesia, kebijakan luar negeri, Laut Natuna Utara